Mathematical Literacy: A Comparative Analysis of School Mathematics Curricula in Indonesia, Singapore, and China - Sumliyah Sumliyah; Iwan Junaedi; Mulyono Mulyono (Jurnal Inovasi Matematika, 2025)
Mathematical literacy is one of the key competencies emphasized in mathematics education. This study aims to describe the development of mathematical literacy within the mathematics curricula of Indonesia, Singapore, and China. The research employs a Systematic Literature Review (SLR) method, supported by content analysis. The findings of this study reveal the following: (1) The mathematics curriculum in Indonesia is highly optimized, with mathematical literacy integrated into the curriculum and learning outcomes tailored to the characteristics of mathematics as a subject (including content and process elements). Singapore constructs mathematical literacy competencies through the establishment of a mathematics curriculum framework that includes concepts, skills, processes, metacognition, and attitudes. Meanwhile, China focuses on improving mathematical literacy by emphasizing problem-solving skills to develop ideas represented as mathematical literacy competencies. (2) The Program for International Student Assessment (PISA) 2022 results indicate Indonesia ranks 70th, Singapore ranks first, and China is divided into several regions, ranking second (Macau), third (Chinese Taipei), and fourth (Hong Kong) out of 80 participating countries. Keywords: Mathematical Literacy, Systematic Literature Review (SLR), Content Analysis, Proportion